Solid-liquid equilibria of binary mixtures of fluorinated ionic liquids - Teles, Ana Rita R.
Within ionic liquids, fluorinated ionic liquids (FILs) present unique physico-chemical properties and potential applications in several fields. However, the melting point of these neoteric compounds is usually higher due to the presence of fluorine atoms. This drawback may be resolved by, for instance, mixing different FILs to create eutectic mixtures. In this work, binary mixtures of fluoro-containing and fluorinated ionic liquids were considered with the aim of decreasing their melting temperatures as well as understanding and characterizing these mixtures and their phase transitions. Five FILs were selected, allowing the investigation of four binary mixtures, each of them with a common ion. Their solid-liquid and solid-solid equilibria were studied by differential scanning calorimetry and the non-ideality of the mixtures was investigated. Overall, a variety of solid-liquid equilibria with systems exhibiting eutectic behavior, polymorphs with solid-solid phase transitions, and the formation of intermediate compounds and solid solutions were surprisingly found. In addition to these intriguing behaviours, novel FILs with lower melting temperatures were obtained by the formation of binary systems, thus enlarging the application range of FILs at lower temperatures.